Prevention, assessment and management of post-dialysis fatigue in patients attending in-center hemodialysis: a best practice implementation project. (November 2016) - Oliver, Veronica; Stephenson, Matthew
EXECUTIVE SUMMARY: Background: The hemodialysis (HD) population experiences a myriad of disease-related symptoms that are often not recognized and/or not treated. Post-dialysis fatigue is a frequent complaint of HD patients following a dialysis session, and there is currently no evidence-based approach to alleviate this problem. Objectives: The object of this best practice implementation project was to implement evidence-based strategies for the prevention, assessment and management of post-dialysis fatigue, with a view to lessening the disease burden experienced by in-center HD patients. Methods: The project used the Joanna Briggs Institute's Practical Application of Clinical Evidence System and Getting Research Into Practice audit tool for promoting change in clinical practice. A baseline audit was conducted, followed by implementation of evidence-based strategies with a focus on staff and patient education. A follow-up audit was performed to assess the effects of the interventions on compliance with best practice. Results: The baseline audit showed that there was no evidence-based approach to prevention, assessment and management of post-dialysis fatigue in place, with only two of the 11 audit criteria showing compliance greater than 50%. Education programs for nursing staff and patients were established, along with the implementation of additional strategies to prevent, assess and manage post-dialysis fatigue. The follow-up audit showed a dramatic increase in the utilization of evidence-based strategies, with ten of the 11 audit criteria achieving above 75% compliance. Conclusion: An evidence-based program to prevent, assess and manage post-dialysis fatigue was successfully implemented. Future studies may reveal if this project has lessened the disease burden experienced by in-center HD patients.